The Analysis Of Mental Health Services For Child Victims Of Sexual Violence At The Integrated Service Center Of The Department Of Women's Empowerment And Child Protection Of Labuhan Batu Selatan Regency - Ritonga, Elin Putri Adelina; Nur Saputri, Ika (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2024)
Background: Sexual violence is any act carried out with the aim of obtaining sexual acts or other acts directed at a person's sexuality using coercion regardless of their relationship status with the victim..Objectives: analyzing Mental Health Services for Child Victims of Sexual Violence at the Integrated Service Center of the Women's Empowerment and Child Protection Service of South Labuhan Batu Regency.Research method: This research is a qualitative descriptive research. This research was conducted qualitatively.Results: The results of this study are From the results of the study conducted by the researcher that the form of mental health services applied at the integrated service center for women's empowerment and child protection in South Labuhan Batu Regency is the approach and assistance model, From the results of the study conducted by the researcher that the mental health service model applied at the integrated service center for women's empowerment and child protection in South Labuhan Batu Regency is individual counseling and the results of the study conducted by the researcher with respondents that the factors that influence the mental health of children who are victims of sexual violence at the Integrated Service Center for Women's Empowerment and Child Protection in South Labuhan Batu Regency are the emergence of feelings of shame and not wanting to socialize with their surroundings